PERAN ACCOUNT REPRESENTATIVE TERHADAP KEPATUHAN WAJIB PAJAK (Studi Kasus Wajib Pajak Orang Pribadi Di KPP Pratama Candisari Semarang) - Ita Wulandari, 11.05.52.0136; Meita, Rachmawati (Students Journal of Accounting and Banking, 2015)
This study aims to examine and analyze service, consultation, and supervision of the Account Representative of taxpayer compliance. The population in this study is the individual taxpayer in the region of KPP Pratama Semarang Candisari. Sampling was done by purposive sampling technique. The number of samples was determined as many as 100 people from the number of individual taxpayers who are on territory of Candisari. Data analysis techniques used in this research is the technique of multiple regression analysis. Finding of this research indicated the service Account Representative influential toward taxpayer compliance. While consulting Account Representative, monitoring Account Representative not influential toward taxpayer compliance.Keywords: Service Account Representative, Consultation Account Representative, Monitoring Account Representative, Tax Compliace